Admission Hyperglycemia Predicts Long-Term Mortality in Critically Ill Patients With Subarachnoid Hemorrhage: A Retrospective Analysis of the MIMIC-III Database - Liu, Dongliang; Tang, Yiyang; Zhang, Qian (Frontiers in Neurology, 2021)
Abstract: Subarachnoid hemorrhage (SAH) is a severe subtype of stroke with high mortality. Hyperglycemia is a common phenomenon in critically ill patients and associated with poor clinical outcome. However, the predictive value of admission hyperglycemia for 30-day and 90-day all caused mortality in critically ill patients with SAH remains controversial. All SAH patients between 2001 and 2012 were included based on the MIMIC-III database and were further classified according to the tertiles of blood glucose (BG) measured on ICU admission. Clinical information including demographic data, comorbidities, and laboratory indicators were exacted and analyzed. The primary outcomes were 30-day and 90-day all-cause mortality. A total of 1298 SAH patients were included. The 30-day and 90-day mortality were 19.80% and 22.73%, respectively. Subjects in the high glucose tertile were older, overweight, had higher SOFA and SAPSII scores and presented higher mortality rate. Generalized additive model revealed a U-shaped relationship between BG and 30-day, 90-day all-cause mortality. Further K-M survival curve also illustrated that subjects with admission hyperglycemia presented lower survival rate and shorter survival time. In Cox analysis, after adjusting potential confounders, glucose was related to an increase in 30-day and 90-day all-cause mortality in SAH patients. In subgroup analysis, the association between SAH and all-cause mortality was consistent. In conclusion, admission hyperglycemia is associated with significantly increased 30-day and 90-day all-cause mortality in critically ill patients with SAH.